133 Development of outpatient based acute heart failure care calls for development of clinical psychology service for whole-person care provision in the UK. (4th June 2021) - Abdullah, Abdullah; Wong, Suzanne; Cleland, John; Wong, Kenneth
Abstract : Introduction: Acute heart failure (AHF) is associated with 7-11% mortality and substantial morbidity. Whole person care of patients with HF is important as depression and hopelessness are prevalent. Patients may feel more hope if they can be successfully treated with IV diuretics at home, in the community or hospital ambulatory care [outpatient management (OPM)]. In 2016, 24% of HF services offered OPM in the UK. Observation studies of OPM suggest substantially lower mortality than IPM data in National HF audits. This suggests observation bias.Aims: To determine: (i) if there has been expansion in OPM service in UK centres; (ii) what proportion of patients are treated with OPM; (iii) what proportion of HF service has clinical psychology support; and (iv) feasibility of conducting a multicentre randomised controlled trial (RCT) in the UK to test safety and cost-effectiveness of OPM. Methods and Results: The 'AHF-IN or OUT-Survey' was sent using Survey Monkey software via the UK HF Investigators Research Network and local Clinical Research Network to hospitals in the UK in 2021.53 responded and estimated 25485 patients with AHF receive inpatient care per year-median 600 per site [IQR 295, 800]: 2730 patients {median 50 [7, 100] per site} are treated per year with OPM, representing 9.7% of the total population of patients who had AHF. 67% (35 of 53) centres provided access to OPM. Of the 17 which do not (33%), 11 of these hope to develop this service while 4 do not know if they should develop this service. Two sites had no intention to develop this service. 4 provide Subcutaneous (SC) diuretics only whilst the majority (31) provide IV diuretic service, including 9 which can deliver both IV and SC Diuretic Service. 28 provide Hospital based OPM ("frusemide lounge"/ambulatory care centre). There are 8 community-based services and 12 sites can deliver parenteral diuretics at home (figure 2). Table 1 shows details of the healthcare professionals who administer outpatient based IV diuretic treatment.Only 19% (10) have clinical psychology service; whilst 75% (39) do not. 6% (3) of respondents are not sure if they have clinical psychology service. We are planning a multicentre RCT to test if indeed OPM of AHF is safe, cost-effective, improves wellbeing and hope. 3573 patients are eligible to take part in the SAFE-RCT over 2 years -median 64 per site [33, 100]. 1501 can be randomised within 2 years {median 20 per site [30, 50]}. Conclusions: Outpatient based IV diuretic therapy is gaining popularity in the UK. Only a small minority of hospitals have clinical psychology service for patients who suffer from HF. Before further rapid expansion of outpatient based IV diuretic service in the UK, a multicentre RCT is urgently needed to test the safety and cost-effectiveness of this innovative service. Importantly, there also needs to be expansion of clinical psychology service alongside in order to provide patients with excellent whole person care Conflict of Interest: No